It's not amalgam, it is white amalgam - Hadeel Arefein; Aljohara Alzuhairi; A. Alowid; S. Khier (Elsevier, 2019)
Introduction: A new class of restorative GIC, named Zirconomer, with increased strength and durability has been developed. It shows strength of amalgam, so it is also called white amalgam. Inclusion of zirconia fillers reinforces the structural integrity of that material, imparts its outstanding posterior esthetics, completely eliminates mercury hazards, and also it is fluoride rich, especially in cases with high caries risk. It is an ideal requirement for restorative material it has a good color stability, a co-efficient of thermal expansion, biocompatibility similar to that of natural tooth, remarkable edge strength, excellent marginal seal, and the ability to adhere chemically to enamel and dentin. Glass ionomer cements are esthetically more pleasing than metallic restorations, on the contrary, their use in dentistry as a restorative material in stress-bearing areas is limited due to poor mechanical properties. New GIC formulations are being introduced every day with improved physical and mechanical properties. Objectives: Zirconomer compared to Amalgam restoration. Materials and methods: Articles found through Medline search; Pubmed, Scopus, Cochrane Library databases covering years starting from 2010 to 2018 were reviewed. Key search words "Zirconomer," "zirconium oxide," "non-metal restorations," "ceramic oxides," "veneering ceramic," "zirconia reinforced glass ionomer cement," "zirconiabased fixed dental prostheses" and silver amalgam were used. Both in-vivo and in-vitro studies into zirconia-based restoration behavior were included. Results: Zirconomer restorations are found to be best alternative now to both GICs with its other modifications as well as dental amalgam for teeth restorations. Some bacterial retention on final could be expected when used. Conclusions: Zirconomer and its family restorations are recommended for restorations of deciduous or permanent teeth. Further in-vitro and in-vivo works are needed to confirm their remarkable behavior. Conflict of interest: The authors declared that there is no conflict of interest.